Pengaruh Variasi Temperatur dan Waktu Tahan Post Weld Heat Treatment pada Kekerasan Material A335 Grade P92 untuk Aplikasi Pembangkit Listrik - Wahyu Restu, Eriek; Wahyudi, M Thariq; Karim, M; Anggara, Dika; Farrasy, Abiyyuda Putra; Luluk Kusminah, Imah; Toto Wibowo, Alvalo (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Perkapalan Negeri Surabaya, 2025)
A335 Grade P92 steel is a martensitic high temperature which widely-applicated on power plan component with high pressure, therefor it required high tightness. Martensitic properties of material caused the high hardness and easily crack. So, Post Weld Heat Treatment is mandatory for A335 Grade P92 welding. This research analyzed the effect of temperature (705°C, 740°C, and 775°C) and holding time (60 and 120 minutes) of post weld heat treatment to hardness. Hardness test result was decreasing with the increasing of temperature and holding time of post weld heat treatment. Weld metal was obtained the highest hardness on specimen with 705°C of temperature and 60 minutes of holding time of post weld heat treatment with 302,85 kgf/mm2, otherwise the lowest hardness was 285,13 kgf/mm2 on 775°C of temperature and 120 minutes of holding time of post weld heat treatment. Microstructure result was obtained of ferrite, pearlite, and martensite on increasing of temperature and holding time of post weld heat treatment which shown the wider of grain.